GELALE: Gelatin dengan Bahan Dasar Tulang Ikan Lele - Aisyah Intani Khoirunnisa'; Julia Nurul Hidayah; Anggitalina Pramilia Dewi; Susanti Rahayu (SMA Trensains Muhammadiyah Sragen, 2024)
Gelatin is a product obtained from the hydrolysis of collagen (the main protein of meat, bones, skin animals) while, collagen is obtained from the extraction process of fresh animal skin, meat and bones. One of the animals that we can use is catfish. Freshwater fish bone waste such as catfish (Clarias sp) has sufficient protein content to be processed into collagen. The manufacture of catfish bone gelatin is carried out by an acid process using 1% hydrochloric acid. The purpose of this study was to determine how to make GELALE (Gelatin with Catfish Bone as a Base Material). Data collection methods using observation methods, and literature studies. The tests carried out were pH test, water content test, organoleptic test. GELALE has a pH of 5, a water content of 11.1% and is characterized by a brownish yellow color and no odor.